Kajian Kinerja Pelayanan Nasabah pada Perseroan Terbatas Bank Sulawesi Utara - Tulangi, I. S. J.; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract. This study intends to determine the front office employee service performance for customers of PT Bank of North Sulawesi. The method used in this study is a qualitative method, with the informant about 20 people consisting of 5 employees and 15 customers. The results indicate an employee at the customer service has to understand the situation and conditions of employment, has been trying to do a good job in accordance with standard operating prosudur. Nevertheless, there are still customers who do not feel satisfied with the quality of service they provide. In general, front office service employees are quite good, but the quality of service needs to be improved so that customer satisfaction can be maintained and even improved.Â Key words: Employee Performance, Services, Customer, Front Office